Między ołtarzem a gabinetem partyjnym. Kościół rzymskokatolicki w sowieckim Lwowie w latach 1953–1959 w świetle raportów pełnomocnika Rady ds. Kultów Religijnych w obwodzie lwowskim - Olechowski, Piotr (Pamięć i Sprawiedliwość, 2017)
The article presents an outline of the history of the Roman Catholic Church in Lviv in 1953-1959. It discusses the history of individual parishes in that city, as well as all attempts at influencing and exposing those religious communities made by the Soviet authorities, for religious activity was especially interesting to Soviet notables. The text also presents the Church’s situation in the light of Soviet legislation. At the time, the term “Catholic” in former Eastern regions of the Polish Republic almost always referred to a person of Polish nationality. Thus, the article can be considered as a presentation of the life of Poles who remained in Lviv until the “second repatriation”. It was the last moment when that community was relatively numerous. As a large proportion of the believers left in the second half of the 1950s, the Polish element became considerably weaker. It obviously led to a change in the Roman Catholic Church’s situation. Nevertheless, a slow suppression of religious activity began much earlier. It grew stronger during the period delimited in the text. The sources on which the article is based include the documents of Soviet provenance (mostly secret internal documents of the local Religious Cult Plenipotentiary). A large portion of them appear in a scholarly publication for the first time.